Can investment in river basins sustain global development of food and energy systems? - Cook, Simon; Fisher, M. (2015)
© 2016 by Taylor & Francis Group, LLC. Yet while the overall threat to resources seems unquestionable, the consequences to food or energy security and the sustainability of development seem less certain. The costs of action to address the problem are large. Uncertainty plays into the hands of the procrastinating politician. Our goal must be to support development that is sustainable and inclusive.